Dynamic capabilities and firm performance: moderated mediation model with product innovation as mediator and technology uncertainty as moderator - Zehir, Cemal; Vural, Sumeyye Cicek (EMERALD GROUP PUBLISHING LTD, 2025)
PurposeThis study aims to explain the relationships between dynamic capabilities, product innovation, firm performance and technology uncertainty.Design/methodology/approachThe quantitative research method was the preferred approach. Data were collected through a questionnaire from managers working in different sectors. The study's sample consists of 619 managers from 226 different firms.FindingsThe findings show that there is a positive relationship between dynamic capabilities and product innovation and that dynamic capabilities have a positive relationship with firm performance. In addition, the findings indicate a significant positive mediating effect of product innovation on the relationship between dynamic capabilities and firm performance. Another key finding is the positive moderation effect of technology uncertainty on the relationship between product innovation and firm performance.Research limitations/implicationsUsing a single sample (country) limits generalizability due to differences in economic structure and market dynamics. Furthermore, by focusing only on product innovation, the role of other types of innovation is not considered.Practical implicationsThis study emphasizes that, especially in environments with high technology uncertainty, it is important to develop dynamic capabilities for better firm performance as well as turn these capabilities into tangible outputs such as product innovation.Originality/valueThis study examines the relationship between dynamic capabilities and firm performance, which is frequently discussed and extremely important for the literature, from different perspectives within the context of an emerging economy. In addition to the direct relationship between dynamic capabilities and firm performance, the contribution of dynamic capabilities to performance through product innovation, which is an ordinary capability, (together with the moderating effect of technological uncertainty) was investigated.
Keywords: Dynamic capabilities; Product innovation; Firm performance; Technology uncertainty; ENTREPRENEURIAL ORIENTATION; ENVIRONMENTAL UNCERTAINTY; IMPACT; MANAGEMENT; SUCCESS; MARKET; ORGANIZATIONS; ECONOMIES; RESOURCES; EVOLUTION; Business & Economics